Identifying queer discourses and navigational strategies in mathematics for undergraduate STEM students - Voigt, Matthew (Frontiers in Education, 2024)
Using phenomenology, this article identifies seven Queer discourses and navigational strategies in mathematics based on individual interviews with 17 Queer STEM students. The most prevalent discourses cast Queer identity as being irrelevant (erasure), unseen (heteronormative), or discriminated against (marginalized) in mathematics. At the same time there were some beliefs that Queer identity acceptance was unknown (ambiguous) was treated equally (normalized) or was accepted and even valued in math. Key findings from the study help theory build an exclusionirrelevancy space to network together mathematical discourses and highlight how Queer marginalization is acted upon based on notions of rightful presence and not mathematical success.